Analysis of the freezeback of water in a cylindrical borehole drilled in an ice sheet - Takagi, Shunsuke. (Hanover, N.H. : Corps of Engineers, U.S. Army Cold Regions Research and Engineering Laboratory, 1974)
Mode of access: Internet.